Optoelectronic properties of low-dimensional Dirac systems - Ng, Raymond Albert L. (Animo Repository, 2024)
The charge carriers in many low-dimensional carbon-based nanostructures behave as ultrarelativistic particles described by the Dirac equation. These systems show tremendous potential for use in next-generation optoelectronic devices, opening a path for wireless communications beyond 5G. In this work, we consider state-of-the-art, recently synthesized molecules such as carbyne and cyclo[n]carbon, as well as tilted 2D Dirac materials like the graphene analogue 8-Pmmn borophene, to probe their optoelectronic properties. For a finite carbyne chain, it is found that the size of the inherent HOMO–LUMO gap and the intensity of interlevel transitions can both be modulated by an external electric field, although its influence is affected by the relative onsite energies at either end of the chain. For an odd-dimered cyclo[n]carbon ring, an analytic model is developed based on the tight-binding formalism, which finds that the symmetry-induced energy level degeneracy which is broken by the Stark effect (in some cases together with Jahn–Teller distortion) leads to emergent doublet states whose energy separation and oscillator strengths are linearly dependent on the magnitude of the applied electric field. For a tilted 2D Dirac system, a general method is developed such that well-known solutions to the differential equations governing confined modes in a graphene waveguide could be repurposed to obtain new solutions to the confinement problem in a 2D system with tilted Dirac cones, such as 8-Pmmn borophene, where a quasi-1D hyperbolic secant guiding potential is shown to enable valley polarization of traveling quasiparticles. The physical insights gained from this work can serve to guide the development of novel terahertz and valleytronics devices based on low-dimensional Dirac systems.